Bacterial dynamics of sugarcane silage in the tropics. (17th February 2021) - Muraro, Gisele Bonato; de Almeida Carvalho‐Estrada, Paula; de Oliveira Pasetti, Maximiliano Henrique; Santos, Mateus Castilho; Nussio, Luiz Gustavo
Summary: The objective of this study was to evaluate changes in the bacterial community in sugarcane silage, in distinct soil types along the storage period. We depicted the bacterial community associated with sugarcane, before and after ensiling, through a massive sequencing of the gene 16S rRNA using MiSeq platform. The ensilage process shifted the composition of the bacterial community from the heterofermentative lactic acid bacteria Leuconostoc to bacteria belonging to the genera Acinetobacter, Ralstonia and Novosphingobium . However, this shift did not convey statically significant differences in alfa diversity metrics. In addition, similarity percentage analysis showed that the bacterial Operational Taxonomic Units that were primarily responsible for the observed differences were Leuconostoc, Pseudomonas, Acinetobacter, Ralstonia, Fructobacillus, Novosphingobium, Lactobacillus, Burkholderia and Clostridium sensu stricto 1 . The storage period was the most important factor responsible for changes in the bacterial community of silages. Results confirmed that the type of soil did not influence the dissimilarity found among samples.